Pharmacological effects of baicalin in lung diseases - Wang, Duoning; Li, Yi (Frontiers in Pharmacology, 2023)
The flavonoid chemical known as baicalin was discovered in the root of Scutellaria baicalensis Georgi, which is widely used in medicine, health care, and food industries. Recently, accumulated investigations have demonstrated that therapeutic benefits of baicalin in treating various lung diseases, due to its antioxidant, anti-inflammatory, immunomodulatory, antioxidant, anti-apoptotic, anticancer and antiviral effects. In this review, we summarized the role that baicalin plays in varieties of lung diseases, including chronic obstructive pulmonary disease, asthma, pulmonary fibrosis, pulmonary hypertension, pulmonary infections, acute lung injury/ acute respiratory distress syndrome, and lung cancer. We also discussed the underlying mechanisms of targeting baicalin for these lung diseases.